Sociology of Law as an International Undertaking - Guibentif, P. (RCSL Newsletter, 2025)
The efforts undertaken by scientists and international organizations to establish the organizational conditions for an international scientific practice enable the scientific community to play a role at the international level which may have an impact beyond the scientific domain. What is at stake is to play this role as productively as possible, in particular at three levels: building an international scientific community; inspiring international collective action; practicing international citizenship. One additional mission, in the case of sociology of law: promoting lay knowledge of the law.